ANALISA PROSES PELIPUTAN BERITA TV MUHAMMADIYAH LAMPUNG EPISODE PERESMIAN PONDOK PESANTREN MUHAMMADIYAH ABU DZAR AL-GHIFARI LAMPUNG TIMUR LAMPUNG 2023 - tyon, bugis adi; fajar, muhammad samson; Nur, Muhammad (INTERCODE, 2024)
The mass media as a means of information is the most important part of human life. Mass media is a medium of communication and information that disseminates information massively or thoroughly. Television is one of the modern communication media whose development is currently very rapid. In addition, television in the process of broadcasting its message is audiovisual, that is, it can be seen and heard. Based on the function of mass media, in this case television plays a role as a transmitter of information, social persuasion, supervision, correlation and social inheritance This research aims to find out the Analysis of the Muhammadiyah Lampung TV News Coverage Process Episode of the Inauguration of the Abu Dzar Al-Ghifari Islamic Boarding School in East Lampung and to find out the factors that can support and hinder the Analysis of the Muhammadiyah Lampung TV News Coverage Process Episode of the Inauguration of the Muhammadiyah Islamic Boarding School Abu Dzar Al-Ghifari East Lampung Lampung 2023. This type of research is descriptive qualitative, namely analyzing, describing and summarizing various conditions, situations from various data collected in the form of interviews or observations regarding the problems being studied that occur in the field. The research results show that the TvMu Lampung news coverage techniques that must be mastered are searching for or determining TV news, writing TV news, interviewing TV news, taking pictures of TV news and editing TV news scripts.The conclusion of this research is that: analysis of the stages of the Muhammadiyah Lampung TV news coverage process. Episode of the Inauguration of Muhammadiyah Abu Dzar Al-Ghifari Islamic Boarding School, East Lampung, namely the pre-production stage, production stage and post-production stage.Keywords: Coverage, TV News, TV Muhammadiyah Lampung